Contradictory hypothesis using coq inversion tactic - coq

From this example:
Example foo : forall (X : Type) (x y z : X) (l j : list X),
x :: y :: l = z :: j ->
y :: l = x :: j ->
x = y.
It can be solved just doing inversion on the second hypothesis:
Proof.
intros X x y z l j eq1 eq2. inversion eq2. reflexivity. Qed.
However, doing inversion also in the first hypothesis, yields apparently contradictory hypothesis:
Proof.
intros X x y z l j eq1 eq2. inversion eq2. inversion eq1. reflexivity. Qed.
Because, in this last proof, the generated hypothesis are:
H0 : y = x
H1 : l = j
H2 : x = z
H3 : y :: l = j
But, if I'm not missing something obvious, it is impossible for both H1 and H3 to be true at the same time.
Can someone explain me what is going on? Is it just that the example is "bad designed" (both hypothesis are contradictory) and that Coq inversion tactic just swallows them? Is it a principle of explosion based on two hypothesis considered together? If so, is it then possible to prove the example just by deriving anything from falsehood? How?

Your example is assuming contradictory hypotheses: they imply that length l + 2 is equal to length l + 1.
Require Import Coq.Lists.List.
Require Import Omega.
Example foo : forall (X : Type) (x y z : X) (l j : list X),
x :: y :: l = z :: j ->
y :: l = x :: j ->
x = y.
Proof.
intros X x y z l j eq1 eq2.
apply (f_equal (#length _)) in eq1.
apply (f_equal (#length _)) in eq2.
simpl in *.
omega.
Qed.
By the principle of explosion, it is not surprising that Coq is able to derive a contradictory context.
Besides this small oddity, there is nothing wrong with the fact that the generated hypotheses are contradictory: such contexts can arise even if the original hypotheses are consistent. Consider the following (admittedly contrived) proof:
Goal forall b c : bool, b = c -> c = b.
Proof.
intros b c e.
destruct b, c.
- reflexivity.
- discriminate.
- discriminate.
- reflexivity.
Qed.
The second and third branches have contradictory hypotheses (true = false and false = true), even if the original hypothesis, b = c, is innocuous. This example is a bit different from the original one, because the contradiction was not obtained by combining hypotheses. Instead, when we call destruct, we promise Coq to prove the conclusion by considering a few subgoals obtained by case analyses. If some of the subgoals happen to be contradictory, even better: there won't be any work to do there.

Related

How to improve this proof?

I work on mereology and I wanted to prove that a given theorem (Extensionality) follows from the four axioms I had.
This is my code:
Require Import Classical.
Parameter Entity: Set.
Parameter P : Entity -> Entity -> Prop.
Axiom P_refl : forall x, P x x.
Axiom P_trans : forall x y z,
P x y -> P y z -> P x z.
Axiom P_antisym : forall x y,
P x y -> P y x -> x = y.
Definition PP x y := P x y /\ x <> y.
Definition O x y := exists z, P z x /\ P z y.
Axiom strong_supp : forall x y,
~ P y x -> exists z, P z y /\ ~ O z x.
And this is my proof:
Theorem extension : forall x y,
(exists z, PP z x) -> (forall z, PP z x <-> PP z y) -> x = y.
Proof.
intros x y [w PPwx] H.
apply Peirce.
intros Hcontra.
destruct (classic (P y x)) as [yesP|notP].
- pose proof (H y) as [].
destruct H0.
split; auto.
contradiction.
- pose proof (strong_supp x y notP) as [z []].
assert (y = z).
apply Peirce.
intros Hcontra'.
pose proof (H z) as [].
destruct H3.
split; auto.
destruct H1.
exists z.
split.
apply P_refl.
assumption.
rewrite <- H2 in H1.
pose proof (H w) as [].
pose proof (H3 PPwx).
destruct PPwx.
destruct H5.
destruct H1.
exists w.
split; assumption.
Qed.
I’m happy with the fact that I completed this proof. However, I find it quite messy. And I don’t know how to improve it. (The only thing I think of is to use patterns instead of destruct.) It is possible to improve this proof? If so, please do not use super complex tactics: I would like to understand the upgrades you will propose.
Here is a refactoring of your proof:
Require Import Classical.
Parameter Entity: Set.
Parameter P : Entity -> Entity -> Prop.
Axiom P_refl : forall x, P x x.
Axiom P_trans : forall x y z,
P x y -> P y z -> P x z.
Axiom P_antisym : forall x y,
P x y -> P y x -> x = y.
Definition PP x y := P x y /\ x <> y.
Definition O x y := exists z, P z x /\ P z y.
Axiom strong_supp : forall x y,
~ P y x -> exists z, P z y /\ ~ O z x.
Theorem extension : forall x y,
(exists z, PP z x) -> (forall z, PP z x <-> PP z y) -> x = y.
Proof.
intros x y [w PPwx] x_equiv_y.
apply NNPP. intros x_ne_y.
assert (~ P y x) as NPyx.
{ intros Pxy.
enough (PP y y) as [_ y_ne_y] by congruence.
rewrite <- x_equiv_y. split; congruence. }
destruct (strong_supp x y NPyx) as (z & Pzy & NOzx).
assert (y <> z) as y_ne_z.
{ intros <-. (* Substitute z right away. *)
assert (PP w y) as [Pwy NEwy] by (rewrite <- x_equiv_y; trivial).
destruct PPwx as [Pwx NEwx].
apply NOzx.
now exists w. }
assert (PP z x) as [Pzx _].
{ rewrite x_equiv_y. split; congruence. }
apply NOzx. exists z. split; trivial.
apply P_refl.
Qed.
The main changes are:
Give explicit and informative names to all the intermediate hypotheses (i.e., avoid doing destruct foo as [x []])
Use curly braces to separate the proofs of the intermediate assertions from the main proof.
Use the congruence tactic to automate some of the low-level equality reasoning. Roughly speaking, this tactic solves goals that can be established just by rewriting with equalities and pruning subgoals with contradictory statements like x <> x.
Condense trivial proof steps using the assert ... by tactic, which does not generate new subgoals.
Use the (a & b & c) destruct patterns rather than [a [b c]], which are harder to read.
Rewrite with x_equiv_y to avoid doing sequences such as specialize... destruct... apply H0 in H1
Avoid some unnecessary uses of classical reasoning.

Relations with dependent types in Coq

I want to define a relation over two type families in Coq and have come up with the following definition dep_rel and the identity relation dep_rel_id:
Require Import Coq.Logic.JMeq.
Require Import Coq.Program.Equality.
Require Import Classical_Prop.
Definition dep_rel (X Y: Type -> Type) :=
forall i, X i -> forall j, Y j -> Prop.
Inductive dep_rel_id {X} : dep_rel X X :=
| dep_rel_id_intro i x: dep_rel_id i x i x.
However, I got stuck when I tried to prove the following lemma:
Lemma dep_rel_id_inv {E} i x j y:
#dep_rel_id E i x j y -> existT _ i x = existT _ j y.
Proof.
intros H. inversion H. subst.
Abort.
inversion H seems to ignore the fact that the two xs in dep_rel_id i x i x are the same. I end up with the proof state:
E : Type -> Type
j : Type
x, y, x0 : E j
H2 : existT (fun x : Type => E x) j x0 = existT (fun x : Type => E x) j x
H : dep_rel_id j x j y
x1 : E j
H5 : existT (fun x : Type => E x) j x1 = existT (fun x : Type => E x) j y
x2 : E j
H4 : j = j
============================
existT E j x = existT E j x1
I don't think the goal can be proved in this way. Are there any tactics for situation like this that I'm not aware of?
By the way, I was able to prove the lemma with a somehow tweaked definition like below:
Inductive dep_rel_id' {X} : dep_rel X X :=
| dep_rel_id_intro' i x j y:
i = j -> x ~= y -> dep_rel_id' i x j y.
Lemma dep_rel_id_inv' {E} i x j y:
#dep_rel_id' E i x j y -> existT _ i x = existT _ j y.
Proof.
intros H. inversion H. subst.
apply inj_pair2 in H0.
apply inj_pair2 in H1. subst.
reflexivity.
Qed.
But I'm still curious whether this can be done in a simpler way (without using JMeq probably?). I'd be grateful for your suggestions.
Not sure what the issue is with inversion, indeed it seems like it has lost track of an important equality. However, using case H instead of inversion H seems to work just fine:
Lemma dep_rel_id_inv {E} i x j y:
#dep_rel_id E i x j y -> existT _ i x = existT _ j y.
Proof.
intros H.
case H.
reflexivity.
Qed.
But having case or destruct do the job where inversion couldn’t is very suprising to me. I suspect some kind of bug/wrong simplification by inversion, as simple inversion also gives a hypothesis from which one can prove the goal.

How to eliminate a disjunction inside of an expression?

Lemma In_map_iff :
forall (A B : Type) (f : A -> B) (l : list A) (y : B),
In y (map f l) <->
exists x, f x = y /\ In x l.
Proof.
split.
- generalize dependent y.
generalize dependent f.
induction l.
+ intros. inversion H.
+ intros.
simpl.
simpl in H.
destruct H.
* exists x.
split.
apply H.
left. reflexivity.
*
1 subgoal
A : Type
B : Type
x : A
l : list A
IHl : forall (f : A -> B) (y : B),
In y (map f l) -> exists x : A, f x = y /\ In x l
f : A -> B
y : B
H : In y (map f l)
______________________________________(1/1)
exists x0 : A, f x0 = y /\ (x = x0 \/ In x0 l)
Since proving exists x0 : A, f x0 = y /\ (x = x0 \/ In x0 l) is the same as proving exists x0 : A, f x0 = y /\ In x0 l, I want to eliminate x = x0 inside the goal here so I can apply the inductive hypothesis, but I am not sure how to do this. I've tried left in (x = x0 \/ In x0 l) and various other things, but I haven't been successful in making it happen. As it turns out, defining a helper function of type forall a b c, (a /\ c) -> a /\ (b \/ c) to do the rewriting does not work for terms under an existential either.
How could this be done?
Note that the above is one of the SF book exercises.
You can get access to the components of your inductive hypothesis with any of the following:
specialize (IHl f y h); destruct IHl
destruct (IHl f y H)
edestruct IHl
You can then use exists and split to manipulate the goal into a form that is easier to work with.
As it turns out, it is necessary to define a helper.
Lemma In_map_iff_helper : forall (X : Type) (a b c : X -> Prop),
(exists q, (a q /\ c q)) -> (exists q, a q /\ (b q \/ c q)).
Proof.
intros.
destruct H.
exists x.
destruct H.
split.
apply H.
right.
apply H0.
Qed.
This does the rewriting that is needed right off the bat. I made a really dumb error thinking that I needed a tactic rather than an auxiliary lemma. I should have studied the preceding examples more closely - if I did, I'd have realized that existentials need to be accounted for.

How to prove theorem about list of pairs

I tried to continue proving this practice example that is about list of pairs, but it seems impossible. How should I continue to solve this theorem?
Require Import List.
Fixpoint split (A B:Set)(x:list (A*B)) : (list A)*(list B) :=
match x with
|nil => (nil, nil)
|cons (a,b) x1 => let (ta, tb) := split A B x1 in (a::ta, b::tb)
end.
Theorem split_eq_len :
forall (A B:Set)(x:list (A*B))(y:list A)(z:list B),(split A B x)=(y,z) ->
length y = length z.
Proof.
intros A B x.
elim x.
simpl.
intros y z.
intros H.
injection H.
intros H1 H2.
rewrite <- H1.
rewrite <- H2.
reflexivity.
intros hx.
elim hx.
intros a b tx H y z.
simpl.
intro.
destruct (split A B tx).
I don't want to just give you a proof, but here's one hint:
Your proof will be a bit simpler if you use inversion H instead of injection H and subst instead of rewriting with equalities (subst takes any equality v = expr where v is a variable and substitutes expr for v everywhere; it then clears out the variable v).
Let me show you a couple of steps you can take to advance your proof.
You have ended up in this proof state:
H0 : (a :: l, b :: l0) = (y, z)
============================
length y = length z
At this point it should be obvious that y and z are some non-empty lists. So injection H0. (or inversion H0. as suggested by Tej Chajed) helps you with this.
Then you can change your goal into
length l = length l0
using a combination of simplifications and rewrites (it depends on the exact tactic you use, inversion makes it simpler). You may also find the f_equal tactic very useful. At this point you are almost done because you can now use your induction hypothesis.

How to deal with a function with an exists on the right side?

I am not sure whether I am using the right words in the question title, so here is the code:
Lemma In_map_iff :
forall (A B : Type) (f : A -> B) (l : list A) (y : B),
In y (map f l) <->
exists x, f x = y /\ In x l.
Proof.
intros A B f l y.
split.
- intros.
induction l.
+ intros. inversion H.
+ exists x.
simpl.
simpl in H.
destruct H.
* split.
{ apply H. }
{ left. reflexivity. }
* split.
A : Type
B : Type
f : A -> B
x : A
l : list A
y : B
H : In y (map f l)
IHl : In y (map f l) -> exists x : A, f x = y /\ In x l
============================
f x = y
Basically, there is not much to go on with this proof, I can only really use induction on l and after substituting for x in the goal I get the above form. If IHl had a forall instead of exists maybe I could substitute something there, but I am not sure at all what to do here.
I've been stuck on this one for a while now, but unlike the other problems where that has happened, I could not find the solution online for this one. This is a problem as I am going through the book on my own, so have nobody to ask except in places like SO.
I'd appreciate a few hints. Thank you.
Lemma In_map_iff :
forall (A B : Type) (f : A -> B) (l : list A) (y : B),
In y (map f l) <->
exists x, f x = y /\ In x l.
Proof.
intros A B f l y.
split.
- intros.
induction l.
+ intros. inversion H.
+ simpl.
simpl in H.
destruct H.
* exists x.
split.
{ apply H. }
{ left. reflexivity. }
* destruct IHl.
-- apply H.
-- exists x0.
destruct H0.
++ split.
** apply H0.
** right. apply H1.
- intros.
inversion H.
induction l.
+ intros.
inversion H.
inversion H1.
inversion H3.
+ simpl.
right.
apply IHl.
* inversion H.
inversion H0.
inversion H2.
exists x.
split.
-- reflexivity.
-- destruct H3.
A : Type
B : Type
f : A -> B
x0 : A
l : list A
y : B
H : exists x : A, f x = y /\ In x (x0 :: l)
x : A
H0 : f x = y /\ In x (x0 :: l)
IHl : (exists x : A, f x = y /\ In x l) ->
f x = y /\ In x l -> In y (map f l)
x1 : A
H1 : f x1 = y /\ In x1 (x0 :: l)
H2 : f x = y
H3 : x0 = x
H4 : f x = y
============================
In x l
I managed to do one case, but am now stuck in the other. To be honest, since I've already spent 5 hours on a problem that should need like 15 minutes, I am starting to think that maybe I should consider genetic programming at this point.
H can be true on two different ways, try destruct H. From that, the proof follows easily I think, but be careful on the order you destruct H and instantiate the existential thou.
Here is a proof that has the same structure as would have a pen-and-paper proof (at least the first -> part). When you see <tactic>... it means ; intuition (because of Proof with intuition. declaration), i.e. apply the intuition tactic to all the subgoals generated by <tactic>. intuition enables us not to do tedious logical deductions and can be replaced by a sequence of apply and rewrite tactics, utilizing some logical lemmas.
As #ejgallego pointed out the key here is that while proving you can destruct existential hypotheses and get inhabitants of some types out of them. Which is crucial when trying to prove existential goals.
Require Import Coq.Lists.List.
Lemma some_SF_lemma :
forall (A B : Type) (f : A -> B) (l : list A) (y : B),
In y (map f l) <->
exists x, f x = y /\ In x l.
Proof with intuition.
intros A B f l y. split; intro H.
- (* -> *)
induction l as [ | h l'].
+ (* l = [] *)
contradiction.
+ (* l = h :: l' *)
destruct H.
* exists h...
* destruct (IHl' H) as [x H'].
exists x...
- (* <- *)
admit.
Admitted.